2021
DOI: 10.1039/d0md00367k
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the HCV NS3–4A protease drug boceprevir as COVID-19 therapeutics

Abstract: α-Ketoamide HCV protease inhibitors covalently bind to SARS-CoV-2 3CLpro. Boceprevir is a particular promising repurposed drug as it potently inhibits cellular viral proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 40 publications
0
83
0
1
Order By: Relevance
“…The viral inhibition was observed not only in translation and release but also in replication, which indicated that hypericin targeted the intracellular replication. In contrast to our previous γ-CoV study [ 23 ], we did not study the apoptosis and oxidative stress in PEDV or TGEV here due to the fact that the direct binding of hypericin onto 3CLpro was reported in SARS-CoV-2 [ 8 , 9 , 10 ], which guided us to validate whether hypericin target to TGEV and PEDV 3CLpro ( Figure 3 , Figures S2 and S3 ). As a consequence, the apoptosis and oxidative stress induction shown in the γ-CoV study might be a secondary effect of 3CLpro inhibition.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The viral inhibition was observed not only in translation and release but also in replication, which indicated that hypericin targeted the intracellular replication. In contrast to our previous γ-CoV study [ 23 ], we did not study the apoptosis and oxidative stress in PEDV or TGEV here due to the fact that the direct binding of hypericin onto 3CLpro was reported in SARS-CoV-2 [ 8 , 9 , 10 ], which guided us to validate whether hypericin target to TGEV and PEDV 3CLpro ( Figure 3 , Figures S2 and S3 ). As a consequence, the apoptosis and oxidative stress induction shown in the γ-CoV study might be a secondary effect of 3CLpro inhibition.…”
Section: Discussionmentioning
confidence: 73%
“…Fluorescence signals were captured with a Ti-S fluorescence microscope (Nikon, Tokyo, Japan). The percentage of viral infected cells was calculated by counting the cells with PEDV N-positive signal and dividing it by the number of DAPI-positive [ 10 ]. For each condition, we chose at least three views with more than 300 DAPI-positive cells and triplicated them to get the standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…We also hypothesized that these compounds, including PF-00835231, might prove to be effective against the mutants as well. Boceprevir, which is a protease inhibitor and was originally used to treat hepatitis, has been well studied to carry an inhibitory potential against the Mpro [24][25][26]. This compound was found to carry a very low affinity against the T190I whilst being the most active against the WT.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Main protease (M pro ) of SARS-CoV-2 is some of the decisive factors in the infectious route of the virus; they have been reported as important targets for therapeutic strategies. 9 Because of discovery of new drugs require long time and expense, searching for new compounds from natural sources known with its high safety and applicability will be a good avenue to treat SARS-CoV-2. In order to quickly discovered lead compounds especially from the promising wild plants for clinical trials, virtual screening study was initiated to identify new drug targeting SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%